The effect of breakfast energy, physical endurance, and speed on physical education learning achievement - Randa Andayana; Alnedral Alnedral; Wilda Welis; Anton Komaini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to reveal the direct and indirect effects, as well as the simultaneous effects between variables. This is a quantitative associative study using a path analysis approach. The population in this study was all 612 Physical Education (PJOK) students at SMAN 5 Batam. A sample of 123 students was taken using purposive sampling. Data were collected using a questionnaire for breakfast energy, a bleep test for physical endurance, a 30-meter run test for speed, and report card scores for learning achievement. The data were analyzed using path analysis through a structural model test at α = 0.05. The results of the hypothesis testing show: (1) there is a direct effect of breakfast energy on PJOK learning achievement (py1 = 0.435 or 18.92%), (2) there is a direct effect of physical endurance on PJOK learning achievement (py2 = 0.564 or 31.08%), (3) there is a direct effect of speed on PJOK learning achievement (py3 = 0.057 or 0.27%), (4) there is an indirect effect of breakfast energy on PJOK learning achievement (p31.py3 = 0.886 or 78.49%), (5) there is an indirect effect of physical endurance on PJOK learning achievement (p32.py3 = 0.0345 total effect 3.49%), and (6) there is a simultaneous effect of breakfast energy, physical endurance and speed on PJOK learning achievement (Rsquare = 0.886 or 88.6%).